2017
DOI: 10.1177/0260106017732719
|View full text |Cite
|
Sign up to set email alerts
|

Special diets in modern America: Analysis of the 2012 National Health Interview Survey data

Abstract: Special diets are mainly used for unspecific health reasons by those who are females, have a college degree or with depression, and commonly used in conjunction with herbs and dietary supplements.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
8
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 27 publications
3
8
1
Order By: Relevance
“…Those 1.12 ± 0.33 1.05 ± 0.29** 0.88 ± 0.27*** 0.96 ± 0.29*** 1.12 ± 0.33 0.99 ± 0.34*** adhering to any special diet, had longer diabetes duration, were more frequently women, and based on the clinical characteristics seemed sicker than the ones not adhering to special diets. Compared to the studies conducted in the general population in Italy (6.2%) [5] and in USA (2.9%) [6], the rate of adhering to special diets, in the current study, was substantially higher. This difference is most likely explained by differences in the study populations.…”
Section: Discussioncontrasting
confidence: 91%
See 2 more Smart Citations
“…Those 1.12 ± 0.33 1.05 ± 0.29** 0.88 ± 0.27*** 0.96 ± 0.29*** 1.12 ± 0.33 0.99 ± 0.34*** adhering to any special diet, had longer diabetes duration, were more frequently women, and based on the clinical characteristics seemed sicker than the ones not adhering to special diets. Compared to the studies conducted in the general population in Italy (6.2%) [5] and in USA (2.9%) [6], the rate of adhering to special diets, in the current study, was substantially higher. This difference is most likely explained by differences in the study populations.…”
Section: Discussioncontrasting
confidence: 91%
“…Moreover, due to the nature of their metabolic disease, individuals with type 1 diabetes may be more aware of the role of the diet for their health, and may be more open to explore the effects of different diets compared to individuals with no particular issues with their health. The female predominance amongst special diet adherents has previously been shown in the American general population [6]. Moreover, in the same study, the highest proportion of individuals adhering to special diets were observed in those aged 50-64 years, and the special diets were mainly used to improve overall health.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…Thereafter, 857 records were excluded by title and abstract reading and 54 full-text articles were assessed for eligibility (see Figure 1): 13 articles were discarded because they did not include a pure vegetarian or vegan diet (i.e. flexitarians or self-reported vegetarians reporting to eat fish) 13,30,[39][40][41][42][43][44][45][46][47][48][49] ; 11 studies had a different objective than the one of our meta-analysis [50][51][52][53][54][55][56][57][58][59][60] ; 6 did not include a control group (omnivorous group) to compare the mental or cognitive outcome [61][62][63][64][65][66] ; 4 had eating disorders as a mental health outcome 67-70 ; 3 were conducted in unhealthy subjects (i.e. papers in which participants reported to have eating disorders before starting the diet) 71-73 , 1 did not provide raw data to extract 60,74 ; 2 were not pure diet interventions in which we could separate individual dietary effects 75,76 ; 1 was not an original article.…”
Section: Search Summarymentioning
confidence: 99%
“…When estimates are driven by online or telephone surveys sponsored by vegetarian associations, the prevalence of self-reported vegetarians can be up to 10-14 % (2)(3)(4)(5) . However, in populationbased studies, national surveys, or independent analysis, only 1-4 % of the population reports following a vegetarian diet (6)(7)(8)(9)(10)(11)(12)(13)(14) .…”
mentioning
confidence: 99%